Dual-reporting transcriptionally linked genetically encoded fluorescent indicators resolve the spatiotemporal coordination of cytosolic abscisic acid and second messenger dynamics in Arabidopsis - Waadt, Rainer; Schumacher, Karin (The plant cell, 2020)
Deciphering signal transduction processes is crucial for understanding how plants sense and respond to environmental changes. Various chemical compounds function as central messengers within deeply intertwined signaling networks. How such compounds act in concert remains to be elucidated. We have developed dual-reporting transcriptionally linked genetically encoded fluorescent indicators (2-in-1-GEFIs) for multiparametric in vivo analyses of the phytohormone abscisic acid (ABA), Ca2+, protons (H+), chloride (anions), the glutathione redox potential, and H2O2. Simultaneous analyses of two signaling compounds in Arabidopsis (Arabidopsis thaliana) roots revealed that ABA treatment and uptake did not trigger rapid cytosolic Ca2+ or H+ dynamics. Glutamate, ATP, Arabidopsis PLANT ELICITOR PEPTIDE, and glutathione disulfide (GSSG) treatments induced rapid spatiotemporally overlapping cytosolic Ca2+, H+, and anion dynamics, but except for GSSG, only weakly affected the cytosolic redox state. Overall, 2-in-1-GEFIs enable complementary, high-resolution in vivo analyses of signaling compound dynamics and facilitate an advanced understanding of the spatiotemporal coordination of signal transduction processes in Arabidopsis.